2020
DOI: 10.1093/jacamr/dlaa049
|View full text |Cite
|
Sign up to set email alerts
|

PRO: The COVID-19 pandemic will result in increased antimicrobial resistance rates

Abstract: We argue that the COVID-19 pandemic will result in increased antimicrobial resistance (AMR). Broad-spectrum antibiotic use is common among hospitalized COVID-19 patients and in excess of reported secondary infection rates, suggesting unnecessary prescribing. Selection pressure is likely to be particularly intense in COVID-19 epicentres and within non-epicentre hospital units dedicated to COVID-19 care. Risk factors that increase the likelihood of hospitalization or poor outcomes among COVID-19 patients, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 16 publications
(24 reference statements)
0
58
1
1
Order By: Relevance
“…Pandemic-associated changes in human behaviour and healthcare practices, including decreased travel, physical distancing, hospital and clinic avoidance, improved infection prevention and control, hand hygiene, and environmental cleaning may alleviate some of the impact of COVID-19 mediated antibiotic use on AMR ( 176 ). However, disproportionately high use of antibiotics in patients with COVID-19 has the potential to exacerbate this public health threat ( 177 ), particularly in areas where AMR is already a significant problem, such as China ( 178 ), Italy ( 179 ), and the US ( 180 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pandemic-associated changes in human behaviour and healthcare practices, including decreased travel, physical distancing, hospital and clinic avoidance, improved infection prevention and control, hand hygiene, and environmental cleaning may alleviate some of the impact of COVID-19 mediated antibiotic use on AMR ( 176 ). However, disproportionately high use of antibiotics in patients with COVID-19 has the potential to exacerbate this public health threat ( 177 ), particularly in areas where AMR is already a significant problem, such as China ( 178 ), Italy ( 179 ), and the US ( 180 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that isolated signs of bCAP cannot be relied upon to make antibiotic decisions in patients with COVID-19. Prior studies [ 9 , 10 , 14 ] have found relatively high rates of antibiotic use in COVID-19 patients, raising concerns for the global impact of the pandemic on driving antimicrobial resistance, as was observed with the SARS-CoV-1 outbreak [ 18 , 19 ]. In our study, most patients without evidence of bCAP and almost half of those with a low suspicion of bCAP had antibiotics discontinued at 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term impact of the COVID-19 pandemic on outpatient antibiotic prescribing and antimicrobial resistance (AMR) trends in the US is uncertain. Antibiotic usage will be influenced by diverse and interacting factors, including the resumption of deferred health care services, new developments in the management of COVID-19 such as validation of immunosuppressive treatments or protective vaccines, the epidemiology of severe acute respiratory syndrome coronavirus 2, influenza and other respiratory tract viral infections in 2020–2021, and indirect effects on public health delivery, health care resources, and economic systems [ 9 ]. Associations between community antibiotic use and AMR are complex, and attempts to evaluate them are complicated by unknown expected effect sizes, costs of surveillance, heterogeneity of clinical and stewardship practices, and other confounding factors [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Associations between community antibiotic use and AMR are complex, and attempts to evaluate them are complicated by unknown expected effect sizes, costs of surveillance, heterogeneity of clinical and stewardship practices, and other confounding factors [ 10 ]. As such, it is an oversimplification to assume that antibiotic prescription trends during the COVID-19 pandemic will correlate directly with AMR rates [ 9 ]. Data have not been published on US in-hospital antibiotic use during the pandemic.…”
Section: Discussionmentioning
confidence: 99%